Applicability of focused Ion beam (FIB) milling with gallium, neon, and xenon to the fracture toughness characterization of gold thin films - Preiß, Eva; Merle, Benoit; Xiao, Yuan; Gannott, Florentina; Liebig, Jan Philipp; Wheeler, Jeffrey M.; Göken, Mathias (Journal of Materials Research, 2021)
Abstract: Focused ion beam (FIB) milling is an increasingly popular technique for fabricating micro-sized samples for nanomechanical characterization. Previous investigations have cautioned that exposure to a gallium ion beam can significantly alter the mechanical behavior of materials. In the present study, the effects of gallium, neon, and xenon ions are scrutinized. We demonstrate that fracture toughness measurements on freestanding gold thin films are unaffected by the choice of the ion species and milling parameters. This is likely because the crack initiation is controlled by the local microstructure and grain boundaries at the notch, rather than by the damaged area introduced by FIB milling. Additionally, gold is not susceptible to chemical embrittlement by common FIB ion species. This confirms the validity of microscale fracture measurements based on similar experimental designs. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-03-05